Commemorative plaque at Hutatma Chowk - Ghosh, Ayan (Jio Institute, 2023)
Commemorative plaque at Hutatma Chowk dedicated to martyrs who laid down their lives, during the Samyukta Maharashtra Movement. The killing of protestors by police garnered major public support for the movement and led to the creation of separate Marathi-speaking Maharashtra state and Gujarati- speaking Gujarat state on 1st May 1960.